IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI KEGIATAN RELIGIUS DI PAUD KASIH IBU PALEMBANG - Permatasari, Desi; Fahmi Padli, Ajie (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA, 2017)
Throughout the history of education in the world, the purpose of education is to make human be smart and good behavior. To make a smart child is not so difficult. However, to make good human beings is not easy and even requires a long process through good habits. Lately a lot of cases of moral decline in the environment of education and society, see the case finally lately the character education is very heavily discussed in the world of education. This research explores the character education implication through religious activity in PAUD Kasih Ibu Palembang. This research uses qualitative. Data obtained by interview and observation. The results obtained indicate that the school is applying character education from an early age through religious activities. The custom-habituation in applied; shake hands, pray at each start and end the activity, perform congregational prayer and read al-quran. And the results felt by teachers and parents are children to be polite, honest, obedient to the teachings of religion, friendly, loving to share, and have a sense of empathy.